Characterization of indigenous Saccharomyces cerevisiae strains for their potential use as Baker’s yeast (Dhaka University Journal of Biological Sciences, 2023)
This research isolated and characterized indigenous Saccharomyces cerevisiae strains. Additionally, this study optimized fermentation conditions for the potential yeast strains and compared their leavening efficacy and biomass production with locally available commercial dried yeast (DY1) in Bangladesh. A total of thirty-five yeast strains were isolated from twenty-five indigenous fruit samples such as Mango (Mangifera indica L.), Jackfruit (Artocarpus heterophyllus Lam.), Papaya (Carica papaya L.), Litchi (Litchi chinensis Sonn.) and Banana (Musa oranta Roxb.). Based on bread leavening efficacy, four potential baker’s yeast strains (Man5, Ban2, Man9, and Ban5) were selected for characterization as potential baker’s yeast. Based on biochemical properties, API kit-based identification, and PCR-based molecular identification, all newly isolated yeast strains were identified as S. cerevisiae. None of these isolates produced H2S. Man5 and Ban5 isolates flocculated at a level comparable to the DY1. All strains showed better temperature tolerance (up to 45°C) than DY1. Man5 and Man9 also showed maximum ethanol tolerance (up to 16%). Only DY1 and Man5 increased dough volume significantly compared with other strains (p< 0.05). Notably, in the optimized growth condition, the Man5 strain produced the highest biomass significantly compared with others (p< 0.05). From the present study, it is concluded that the indigenous strain Man5, Man9, and Ban5 have the potential to be used in the industry as a substitute for imported baker’s yeast in Bangladesh and that will save a substantial amount of foreign currency.Dhaka Univ. J. Biol. Sci. 32(2): 211-223, 2023 (July)